Dissolution and Consequent Morphological Evolution of Electrodeposited Pt−Cu Nanoparticles under Potential Cycling in 0.5 M H2SO4 Solution. Issue 11 (29th April 2019) - Shigihara, Yuichi; Ooi, Azusa; Tada, Eiji; Nishikata, Atsushi
Abstract : The dissolution behavior of Pt−Cu nanoparticles prepared by pulse-electrodeposition under potential cycling was investigated. Electrodeposited Pt−Cu consisted of numerous Pt−Cu nuclei (∼3 nm in diameter) that agglomerated to form larger secondary particles (30–50 nm), and its composition were determined to be Pt−35 at% Cu (Pt−35Cu). A Pt−enriched shell formed on the Pt−35Cu surface due to Cu-selective dissolution from Pt−35Cu during the initial immersion in 0.5 M H2 SO4 . Cu dissolution from Pt−35Cu was then strongly suppressed under potential cycling between 0.05−0.6 and 1.0 V, owing to the Pt−enriched shell. On the contrary, when Pt−35Cu was potential-cycled between 0.05 and 1.4 V, Cu-selective dissolution was not suppressed because Pt dissolved from Pt−35Cu even after the Pt−enriched shell formation. Surface morphology changes during potential cycling were strongly related to both upper ( E L ) and lower ( E U ) potential limits. Surfaces of Pt−35Cu were smoothened when E U = 1.0 and 1.4 V, than when E U = 0.6 V. When E L was fixed at 0.6 V to prevent the dissolved Pt ions from re-depositing on the surface, surface smoothening of Pt−35Cu did not occur during potential cycling between 0.6−1.0 V. Based on these results, the dominant factor for surface reconstruction of Pt−35Cu was Pt dissolution and re-deposition.